Inheritance Portion of The Heir of Women is More Than Men in Islamic Legal Perspective - Muhammad Lutfi Hakim; Mutmainah Mutmainah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, Indonesia, 2021)
The distribution of inheritance in Islam recognizes the principle of ijbari, namely the transfer of inherited property to its heirs, which has been determined in Islamic law covering aspects of heirs, legacy, part of inheritance, and heirs. Regarding the division of legacy between male and female heirs, there is a principle of li al-dzakari mitsl al-hadz al-untsaian (the male part is like two female parts). Unfortunately, the provision is not applied in the distribution of inheritance in Enau River Village, which gives the portion of inheritance to girls more than 2:1 than boys. This paper aims to describe the practice of heritage sharing in Sungai Enau Village because of and alternative distribution of legacy its heritage following Islamic law. The results of this paper found that some Muslim communities in Sungai Enau village are majority Muslim (65%) their inheritance by a method of internal family deliberation with the consent of all heirs. The result of this deliberation is that the heir son gets a share of the inheritance more than twice as much as the heir son. The main reason for giving a portion of the inheritance to girls is more than twice as much as boys are that girls care more, help more, and take care of their parents (especially heirs) than boys. Although the provision is not following the opinion of the majority of jurists of scholars who give inheritance to the heir’s men are twice as much as women (2:1), and that is following the principle of li al-dzakari mitsl al-hadz al-untsaian. Still, the division meets the heir’s sense of justice for the heirs and is supported by local religious leaders’ opinions. This paper analyzes the case and provides an alternative to the distribution of inheritance following the jurists’ views.